Capacitive effects in pinpin photodiodes - Fantoni, Alessandro (2013)
The application of a-SiC:H/a-Si:H pinpin photodiodes for optoelectronic applications as a WDM demultiplexer device has been demonstrated useful in optical communications that use the WDM technique to encode multiple signals in the visible light range. This is required in short range optical communication applications, where for costs reasons the link is provided by Plastic Optical Fibers. Characterization of these devices has shown the presence of large photocapacitive effects. By superimposing background illumination to the pulsed channel the device behaves as a filter, producing signal attenuation, or as an amplifier, producing signal gain, depending on the channel/background wavelength combination. We present here results, obtained by numerical simulations, about the internal electric configuration of a-SiC:H/a-Si:H pinpin photodiode. These results address the explanation of the device functioning in the frequency domain to a wavelength tunable photo-capacitance due to the accumulation of space charge localized at the bottom diode that, according to the Shockley-Read-Hall model, it is mainly due to defect trapping. Experimental result about measurement of the photodiode capacitance under different conditions of illumination and applied bias will be also presented. The combination of these analyses permits the description of a wavelength controlled photo-capacitance that combined with the series and parallel resistance of the diodes may result in the explicit definition of cut off frequencies for frequency capacitive filters activated by the light background or an oscillatory resonance of photogenerated carriers between the two diodes. (C) 2013 Elsevier B.V. All rights reserved.